Neurological symptom burden impacts survival prognosis in patients with newly diagnosed non–small cell lung cancer brain metastases. Issue 19 (17th July 2020) - Steindl, Ariane; Yadavalli, Sarah; Gruber, Katharina‐Anna; Seiwald, Maria; Gatterbauer, Brigitte; Dieckmann, Karin; Frischer, Josa M.; Klikovits, Thomas; Zöchbauer‐Müller, Sabine; Grisold, Anna; Hoda, Mir Ali Reza; Marosi, Christine; et al.
Abstract : Background: Brain metastases (BM) are a frequent complication of advanced cancer and are characterized by a variety of neurological symptoms. Although the presence of neurological symptoms is included in the response assessment in patients with primary brain tumors, to the authors' knowledge little is known regarding the prognostic impact of neurological symptoms in patients with BM. Methods: Patients with newly diagnosed BM from non–small cell lung cancer were identified from the Vienna Brain Metastasis Registry and were evaluated according to the incidence, distribution, and prognostic impact of neurological symptoms at the time of diagnosis of BM. Results: A total of 1608 patients (57.3% male and 42.7% female; median age, 62 years) were available for further analyses. Neurological symptoms including focal deficits (985 patients; 61.3%), signs of increased intracranial pressure (483 patients; 30.0%), epileptic seizures (224 patients; 13.9%), and neuropsychological symptoms (233 patients; 14.5%) were documented in 1186 of the 1608 patients (73.8%). Patients with asymptomatic BM presented with a longer median overall survival after the diagnosis of BM compared with patients with symptomatic BM (11 months vs 7 months; P  < .001). In multivariate analysis with a diagnosis‐specific graded prognostic assessment (hazard ratio, 1.41; 95% CI, 1.33‐1.50 [ P  < .001]), the presence of neurological symptoms (hazard ratio, 1.39; 95% CI, 1.23‐1.57 [ P  < .001]) was found to be independently associated with survival prognosis from the time of diagnosis of BM. Conclusions: Neurological symptoms at the time of BM diagnosis demonstrated a strong and independent association with survival prognosis. The results of the current study have highlighted the need for the integration of the presence of neurological symptoms into the prognostic assessment of patients with BM from non–small cell lung cancer. Lay Summary: Neurological symptom evaluation is included regularly in the assessment of patients with primary brain tumors. However, to the authors' knowledge, little is known regarding the prognostic impact in patients with newly diagnosed brain metastases (BM). The current study has provided a detailed clinical characterization of the incidence, distribution, and prognostic impact of neurological symptoms in a large, real‐life cohort of patients with BM from non–small cell lung cancer. In this cohort, neurological symptoms at the time of diagnosis of BM demonstrated a strong, independent prognostic impact on the survival prognosis. The results of the current study have highlighted the need for the integration of neurological symptom burden into the prognostic assessment of patients with BM from non–small cell lung cancer. Abstract : Neurological symptoms at the time of diagnosis of brain metastases demonstrate a strong, independent prognostic impact on prognosis. The current study highlights the integration of neurological symptom burden into the prognostic assessment of patients with brain metastases from non–small cell lung cancer.